From leaves to microbes: How diet and season shape the fecal microbiome of captive Coquerel´s Sifakas (Propithecus coquereli) - Schweikhard, Jonas; Pauly, Andreas; Dierkes, Paul Wilhelm; Zoelzer, Franziska (Frontiers in Microbiomes, 2025)
The community of microorganisms occurring in the animal gut, known as the gut microbiota, is closely connected to host health. It is essential for metabolic processes, digestion, and defense against pathogens. Knowledge about the composition of an intact gut microbiota, along with its natural fluctuations and diversity, is a crucial aspect of proper husbandry and breeding of animals in human care. In this study, we analyzed the fecal microbiota of the critically endangered Coquerel’s sifaka (Propithecus coquereli), with a special focus on seasonal effects and the impact of dietary variations. As a tropical species, European winters may influence microbiota diversity or composition, highlighting the importance of this assessment. Ninety-seven fecal samples collected from all individuals housed in European zoos revealed high microbial diversity and variation. Some of the core taxa present in every sample included Lachnospiraceae, Erysipelotrichaceae, Clostridiaceae, and Bacillaceae. Microbial α-diversity showed no decline in winter, indicating no seasonal effect caused by dietary changes. However, results suggest compositional differences between seasons, indicated by significant differences in β-diversity. These findings confirm the importance of longitudinal studies to fill knowledge gaps between sampling intervals and to characterize microbiota oscillations throughout the year.